2022
DOI: 10.3389/frph.2022.1029381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracytoplasmic sperm injection in women with non-male factor infertility: A systematic review and meta-analysis

Abstract: ObjectiveThe purpose of this study is to determine whether intracytoplasmic sperm injection (ICSI) is beneficial in patients with non-male factor infertility.MethodsThis systematic review and meta-analysis included articles from inception to May 2022. Published studies of non-male factor infertile women undergoing ICSI or in vitro fertilization (IVF) included in PubMed, Embase, web of science, Wanfang Database, and CNKI were searched by computer, without language restrictions. A random-effect model was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In practice, the freeze-all strategy can reduce the risk of ovarian hyperstimulation syndrome (OHSS) in the ovarian stimulation cycle by avoiding pregnancy and obtaining better results [ 39 ]. However, the results of a previous meta-analysis showed no differences in fertilization rate, total fertilization failure rate, good embryo quality rate, fresh embryo implantation clinical pregnancy rate, fresh embryo transfer live birth rate, miscarriage rate, neonatal preterm birth rate and neonatal low birth weight rate in those treated with ICSI compared with IVF [ 40 ]. The relationship between the fertilization method and live birth needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the freeze-all strategy can reduce the risk of ovarian hyperstimulation syndrome (OHSS) in the ovarian stimulation cycle by avoiding pregnancy and obtaining better results [ 39 ]. However, the results of a previous meta-analysis showed no differences in fertilization rate, total fertilization failure rate, good embryo quality rate, fresh embryo implantation clinical pregnancy rate, fresh embryo transfer live birth rate, miscarriage rate, neonatal preterm birth rate and neonatal low birth weight rate in those treated with ICSI compared with IVF [ 40 ]. The relationship between the fertilization method and live birth needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…We used controlled ovary stimulation for ICSI and gonadotropin-releasing hormone agonists or antagonists to prevent premature ovulation. Follicle-stimulating hormone injections were administered until the follicular diameter of 18 mm was reached (Huang et al, 2022;Ribeiro & Sousa, 2023;Rodriguez-Wallberg et al, 2022). A 10000-unit human chorionic gonadotropin (hCG) was injected and after 36 hours the oocytes were retrieved using a transvaginal ultrasound probe to guide a specialized needle through the vaginal wall and into the ovaries and were fertilized with husband sperms.…”
Section: Artmentioning
confidence: 99%
“…[10][11][12] Further, the applicability of the evidence is also limited by the methodological quality of the reviews, for instance, pooling estimates from randomized and observational studies, introducing selection bias and reducing credibility, and relying on laboratory surrogate outcomes rather than patient important outcomes to draw conclusions. [9][10][11][12] Recently, several new randomized controlled trials (RCTs) are accessible and yielded more reliable ICSI results. [13][14][15][16] Therefore, it is necessary to conduct a new systematic review and meta-analysis of RCTs to avoid the above limitations in existing reviews to provide robust evidence clarifying the efficacy of ICSI in non-male factor infertility couples.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, other reviews suggested that ICSI offers no obvious advantage regarding FR and CPR. [10][11][12] Further, the applicability of the evidence is also limited by the methodological quality of the reviews, for instance, pooling estimates from randomized and observational studies, introducing selection bias and reducing credibility, and relying on laboratory surrogate outcomes rather than patient important outcomes to draw conclusions. [9][10][11][12] Recently, several new randomized controlled trials (RCTs) are accessible and yielded more reliable ICSI results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation